A Sociolinguistic Study of Muslim and Christian Wedding Invitation Genre in the Jordanian Society - Mohammed Sawalmeh, Murad Hassan (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study aims at examining the generic structure of Muslim and Christian wedding invitation genre in the Jordanian society. It is a sociolinguistic study. The researcher believes that considering many aspects of these invitation cards such as form, structure and so forth, may provide a lot of information about the social dimensions of those who tend to hold a wedding ceremony. The data are elicited through a questionnaire that consists of twenty-five items compiled from invitation cards for both Muslims and Christians. The findings of the study show that the form of the invitation cards in Islam and Christianity in the Jordanian society is systematic and influenced by social, economic, and religious factors. Finally, this study recommends that further research to be conducted investigating other invitation cards for other events in the Jordanian society such as invitation cards for attending meetings, lectures, celebrations, royal feasts, tribal reconciliation, etc.